PELATIHAN PEMBUATAN MOL NASI BASI GUNA MENDUKUNG PENGELOLAAN LIMBAH ORGANIK DI DESA BATU HIJAU KABUPATEN BONE BOLANGO: TRAINING ON MAKING MOL BASI RICE TO SUPPORT ORGANIC WASTE MANAGEMENT IN BATU HIJAU VILLAGE, BONE BOLANGO REGENCY - Muhammad iqbal Jafar; Muh. Sabir; Fitra Ramadhan Hikaya; Syamsir Syamsir; Asniwati Zainuddin (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
The existence of waste is a problem faced by society today, both in urban and coastal areas, where the largest source of waste comes from household activities in the form of organic waste. Batu Hijau Village, Bone Bolango Regency, is an area in Gorontalo Province which is located in a coastal area which is facing problems related to the presence of household waste which causes pollution to the environment, even though the organic waste can be used as a material that has useful value. One household waste that can be processed into useful products is stale rice. Through training programs to produce local microorganisms (MOL) in partnership with Dasawisma and Karang Taruna in Batu Hijau Village, stale rice waste can be converted into a bioactivator for making organic fertilizer, a plant growth stimulant, and a biological agent for controlling disease in cultivated plants so that the problem of the presence of organic waste polluting the environment can be addressed while also meeting the fertilizer needs of Karang Taruna and Dasawisma partners who carry out cultivation activities in their yards. The results of service program activities based on achievement indicators show that Dasawisma and Karang Taruna partners have increased their knowledge capacity, this can be seen from the partners' ability to adopt the technology for making MOL stale rice. The recommendation for this activity is education on making MOL not only from stale rice but also training regarding making MOL from other materials such as fruit waste and banana tubers